Peran Literasi Budaya dalam Pembentukan Karakter Mahasiswa Calon Pendidik - Anas; Rismawati; Faradilla (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2024)
This study examines the role of cultural literacy in character building among students of the Faculty of Teacher Training and Education at Lakidende University, specifically within the Indonesian Language and Literature Education Study Program. Cultural literacy, encompassing the understanding, appreciation, and application of local and national cultural values, is considered a crucial factor in shaping students’ character, particularly in the context of Indonesia’s cultural diversity. Employing a qualitative approach, this research integrates in-depth interviews, participant observations, and questionnaire distribution among students and lecturers to gain comprehensive insights. The findings reveal that cultural literacy significantly contributes to the development of integrity, ethical awareness, and tolerance among students in the Indonesian Language and Literature Education Study Program. Students who are consistently exposed to cultural literacy demonstrate a deeper understanding of social and moral values and exhibit more positive behaviors in their daily interactions. Moreover, the integration of cultural literacy within the Educational Literacy course and the Tolaki Language and Culture course in the fifth semester reinforces students’ cultural identity and enhances their engagement in the learning process. This study underscores the necessity for higher education institutions in Indonesia to further integrate cultural literacy into the academic framework. Such an initiative not only fosters students' cultural awareness and character development but also serves as a strategic effort to preserve cultural heritage in the face of globalization.